(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The optimum air temperature in a pigsty for sows is 16-18 °C, but during the first days of new born piglets life the temperature in their lairs ought to be 32...34 °C. Therefore the local warming for piglets is installed. The goal o f the investigation was to measure the intensity o f heat irradiation under different lands of infra-red heaters, more often used on Latvia farms. An autonomous infra-red piglet warming systems have been developed. The experiment has showed, that during the first days of piglets life the heater should be kept at the high, so that the irradiated area 0.3— 0.4 m has been. Gradually heaters have to be lifted up 3-4 times while the warming area is 0.6-0.7 m2 in 40-45 days, when piglets are weaned. The temperature in a lair has to be regulated by change o f electric power o f the heater. Several constructions of voltage regidators are worked out, which are able to ensure the temperature on the warmed surface automatically or manually, depending on the temperature in a pigsty and live mass of piglets. The automatic power regulation o f the heaters decreases the consumption of electric energy more than 2 times.